Prediction of Hernia Formation or Cracking of Boiler Water Tubes due to Corrosion - Traore, Sibiri (European Scientific Journal, ESJ, 2025)
This work is part of the preventive maintenance of steam power plant equipment and installations. In boiler water pipes, hernia formation, cracking and perforation are recurrent and occur when the thermal power plant is operating at full capacity. This damage is largely due to corrosion and thinning of the tube wall. When corrosion progresses, the thinning of the tubes progresses simultaneously. From a certain value of the wall thickness, under the effect of water/steam pressure, the tubes deform and burst. In such a situation, it is important to predict approximately when these damages will occur, so that appropriate maintenance measures can be undertaken. For this, we seek to determine the corrosion rate and stresses in the tubes due to water/steam pressure, with a view to finding the maximum time limit not to exceed when replacing the tubes. Among the various methods for determining corrosion rate, it is the method based on weight measurement that has attracted our attention. Tube coupons were taken from a corroded boiler tube and from a new tube of the same characteristics, thus avoiding a study over a very long period, since corrosion takes several years to produce its mechanical effects. Knowing the difference in weight between a coupon of the new tube and that of the corroded tube, and the time of exposure of the tubes until damage, it became easy to determine the corrosion rate. From the corrosion rate and the calculation of stresses in the corroded tube, the maximum time limit to be exceeded for replacing tubes was determined, that is a maximum operating period of 10 years. The tubes must be replaced, in preventive maintenance, before the end of this time limit to prevent the aforementioned damage.